Implementation of Contextual Learning Model of Islamic Religious Education at SMP Negeri 2 Wuryantoro - Sailirrohmah, Hajar; Azani, Mohammad Zakki (Cetta: Jurnal Ilmu Pendidikan, 2025)
The contextual learning model is an approach designed with the aim of making the learning process relevant to the reality of students' lives. It does not only emphasize cognitive understanding, but also emphasizes affective and psychomotor understanding. The contextual learning model provides innovation in Islamic Religious Education learning, especially in students' understanding. This study aims to describe the implementation of the contextual learning model, supporting factors and obstacles to the implementation of the contextual learning model of Islamic religious education at SMP Negeri 2 Wuryantoro. The research approach used is phenomenology with a qualitative research type. Data were collected through observation, interviews, and document studies. Data analysis carried out was data reduction, data presentation and drawing conclusions. The results of the study stated that the implementation of the contextual learning model of Islamic Religious Education in the school had implemented seven components of contextual learning, including constructivism, finding, asking, learning communities, modeling, reflection, and authentic assessment. The components of the learning community and modeling have proven to be very effective in making the learning process more relevant which encourages the development of student character and the need for real examples. In conclusion, the combination of contextual components makes learning more meaningful and relevant. In addition, there are supporting factors, namely curriculum, educators, facilities and infrastructure, and the environment, while inhibiting factors include interests, intelligence, motivation, and attitudes or behavior of students, so educators must also provide guidance to ensure that students are able to understand the meaning of learning.